Discovery of MicroRNAs and Their Target Genes Related to Drought in Paulownia “Yuza 1” by High-Throughput Sequencing - Minjie Deng; Yabing Cao; Zhenli Zhao; Lu Yang; Yanfang Zhang; Yanpeng Dong; Guoqiang Fan (International Journal of Genomics)
Understanding the role of miRNAs in regulating the molecular mechanisms responsive to drought stress was studied in Paulownia “yuza 1.” Two small RNA libraries and two degradome libraries were, respectively, constructed and sequenced in order to detect miRNAs and their target genes associated with drought stress. A total of 107 miRNAs and 42 putative target genes were identified in this study. Among them, 77 miRNAs were differentially expressed between drought-treated Paulownia “yuza 1” and the control (60 downregulated and 17 upregulated). The predicted target genes were annotated using the GO, KEGG, and Nr databases. According to the functional classification of the target genes, Paulownia “yuza 1” may respond to drought stress via plant hormone signal transduction, photosynthesis, and osmotic adjustment. Furthermore, the expression levels of seven miRNAs (ptf-miR157b, ptf-miR159b, ptf-miR398a, ptf-miR9726a, ptf-M2153, ptf-M2218, and ptf-M24a) and their corresponding target genes were validated by quantitative real-time PCR. The results provide relevant information for understanding the molecular mechanism of Paulownia resistance to drought and reference data for researching drought resistance of other trees.